Further research on the cross-cultural application of cognitive consistency theory - Chrysostomos, Archimandrite; Khokhlov, Nikolai E. (The Greek Review of Social Research, 1981)
An experiment was conducted to test the notion that cognitive consistency is not a universal attribute, but is contingent upon such variables as cultural group, age, sex of subject, and the issue under consideration. In a 2 x 2 x 3 x 3 x 2 factorial design, North American and Cypriot subjects were given questionnaires which measured attitudes on three issues before and after the introduction of a discrepant cognition. Subjects differed in evidencing cognitive consistency, or discrepancy-induced attidude change, with age and type of issue interacting with the cultural group. The sex of subjects also mediated the consistency effect, but yielded no significant interaction with the cultural group. The implications of the results for cognitive consistency theory were discussed. Findings replicate data presented in earlier studies with Greek and American populations reported in The International Journal of Psychology, The Greek Review of Social Research, and elsewhere by the same authors.